Treatment of lumbar and intrathoracic meningocele: bioethical implications - Tornali, Cristina; Pratico', Andrea; Vecchio, Flavio; Polizzi, Agata; Ruggieri, Martino; Vecchio, Ignazio (Acta Biomedica Atenei Parmensis, 2021)
Myelomeningocele is a congenital malformation caused by a developmental defect of the spinal cord structures. The exactcause is unknown, but different factors have been involved includingradiation, malnutrition, drugs. Myelomeningocele can develop at any point in the spine, but the lumbosacral region is affected in over 75% of cases. Chest X-raysand computed tomography study are mandatory to reveal tracheal malformations or associatedanomaliesof the ribs. Treatment of myelomeningocele must be multidisciplinary and involve at the same time neurologists, radiologists, neurosurgeons, thoracic surgeons, bioethical experts and take care of the childand also of the family. Some experiences concern the possibility of a in-utero correction of myelomeningocele, in order to avoiding serious and progressive damages to the nervoussystem. Given the improvement of myelomeningocele management, the quality of life is nowadays more acceptable than in the past; however, some severe forms of myelomeningocele cannot still be corrected: in this cases, a “non-interventional” approach may require a form of passive euthanasia that should be discussed and approved with and by parents and Any dissent of the parents must be respected and considered reasonable. The choice of a “non-intervention”, which should be guaranteed to all the people capable of self-determination, is not however so immediate and direct in the case of the minor: the dissent expressed on his behalf by the parents or legal representative may be ethically difficult to be accepted.In this case, the best interest of the child must prevail as the goal of any therapeutic choice.